Hester van Eeghen : bag and shoe design. - Gannij, Joan, ....- (Amsterdam : Bis Publishers, 2008)
Hester van Eeghen has been designing leather bags, wallets, accessories and shoes for twenty years already. She has been described as one of the most influential Dutch designers of the twentieth century. This is her first book featuring a beautifully photographed overview of her work. Geometric shapes and prolific colours characterize her works which often contains a surprise effect or hidden feature. The objects are all designed in Amsterdam and manufactured in limited editions in specialized workshops in Italy, each in a variety of colour combinations. Every item is hand-crafted in supple full grain leather and lined either with leather or natural fabrics. Hester van Eeghen's designs are for sale in over 150 museum and design shops in the Netherlands, Belgium, USA, UK, Germany, Switzerland and Japan